2014
DOI: 10.1111/codi.12687
|View full text |Cite
|
Sign up to set email alerts
|

The influence of laparoscopy on incisional hernia rates: a retrospective analysis of 1057 colorectal cancer resections

Abstract: Aim The aim of this study was to evaluate the incidence of incisional hernia formation after laparoscopic and open surgery for colorectal cancer. Clinical notes and serial computed tomography scans were reviewed, with any incisional hernia including those at a surgical incision, port site, stoma and stoma closure site identified and the size of the defect measured.Results The overall incisional hernia rate was 14.8%. There was no significant difference between the open and laparoscopic groups (14.4% vs 15.9%, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
24
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 23 publications
2
24
0
2
Order By: Relevance
“…Twenty studies did not mention detection methods and, therefore, it seems likely to assume that imaging was not used in these studies. To investigate potential underestimation, the overall incidence of SSIH from the 11 studies with SSIH as the primary outcome was calculated (17.7%, range 1.7%–36.1%) . These rates indeed support the hypothesis that the overall incidence of hernia from all included studies (6.5%), as from those only reporting on SSIH as a secondary outcome (3.6%), is an underestimation.…”
Section: Discussionmentioning
confidence: 76%
“…Twenty studies did not mention detection methods and, therefore, it seems likely to assume that imaging was not used in these studies. To investigate potential underestimation, the overall incidence of SSIH from the 11 studies with SSIH as the primary outcome was calculated (17.7%, range 1.7%–36.1%) . These rates indeed support the hypothesis that the overall incidence of hernia from all included studies (6.5%), as from those only reporting on SSIH as a secondary outcome (3.6%), is an underestimation.…”
Section: Discussionmentioning
confidence: 76%
“…They concluded that these findings led to a weaker abdominal wall and, at least in part, explained the increased incidence of incisional herniation after stoma formation. In a similar vein, a retrospective UK study documents that parastomal herniation is more prevalent (but midline herniation similar) even after laparoscopic colorectal resection . The stomas in these series, to the best of our knowledge, were raised using the traditional ‘through’ rectus abdominis muscle trephine.…”
mentioning
confidence: 83%
“…В то же время испанские специалисты на основании 19-месячного проспективного наблюдения диагностировали вентральные грыжи после открытого и лапароскопического вмешательств по поводу колоректального рака в 40,9 и 37,1 %, соответственно (разница статистически незначима, p = 0,41) [15]. Также не обнаружили достоверной разницы в частоте возникновения вентральных грыж у пациентов с колоректальным раком в зависимости от вида доступа исследователи из Великобритании [16]. Авторы из Сеула опубликовали в 2018 г. результаты общенационального трехгодичного исследования, включавшего 24 645 пациентов, оперированных по поводу злокачественных заболеваний толстой кишки.…”
unclassified
“…Развитие парастомальных грыж при лечении колоректального рака -следующая проблема, волнующая хирургов, так как оперативное лечение этих дефектов брюшной стенки сопряжено с высоким риском инфицирования и развития стриктуры колостомы, что ухудшает качество жизни пациентов. По данным A. Mishra et al [16], H. Hino et al [19] и K. Kojima et al [20], парастомальные грыжи чаще возникают после лапароскопических, а не традиционных вмешательств: 40 и 13 % случаев, соответственно. Эту тенденцию подтверждают P. Andersen at al.…”
unclassified